Solvent-free dynamic nuclear polarization enhancements in organically modified mesoporous silica. Issue 22 (24th May 2021) - de Oliveira, Marcos; Herr, Kevin; Brodrecht, Martin; Haro-Mares, Nadia B.; Wissel, Till; Klimavicius, Vytautas; Breitzke, Hergen; Gutmann, Torsten; Buntkowsky, Gerd
Abstract : NMR signals of organic molecules covalently attached to SBA-15 are efficiently enhanced by solvent free DNP. Carboxy-Proxyl moieties, also grafted to the pore surface are used as polarization source. Abstract : High-field dynamic nuclear polarization is a powerful tool for the structural characterization of species on the surface of porous materials or nanoparticles. For these studies the main source of polarization are radical-containing solutions which are added by post-synthesis impregnation of the sample. Although this strategy is very efficient for a wide variety of materials, the presence of the solvent may influence the chemistry of functional species of interest. Here we address the development of a comprehensive strategy for solvent-free DNP enhanced NMR characterization of functional (target) species on the surface of mesoporous silica (SBA-15). The strategy includes the partial functionalization of the silica surface with Carboxy-Proxyl nitroxide radicals and target Fmoc-Glycine functional groups. As a proof of principle, we have observed for the first time DNP signal enhancements, using the solvent-free approach, for 13 C 1 H CPMAS signals corresponding to organic functionalities on the silica surface. DNP enhancements of up to 3.4 were observed for 13 C 1 H CPMAS, corresponding to an experimental time save of about 12 times. This observation opens the possibility for the DNP-NMR study of surface functional groups without the need of a solvent, allowing, for example, the characterization of catalytic reactions occurring on the surface of mesoporous systems of interest. For 29 Si with direct polarization NMR, up to 8-fold DNP enhancements were obtained. This 29 Si signal enhancement is considerably higher than the obtained with similar approaches reported in literature. Finally, from DNP enhancement profiles we conclude that cross-effect is probably the dominant polarization transfer mechanism.